Determining the Investment Impact of Bulgaria’s 2007 - 2008 Income Tax Reforms - VASILEV, Aleksandar (Journal of Advanced Studies in Finance; Vol 10 No 2 (2019): JASF Volume X Issue 2(20) Winter 2019DO - 10.14505//jasf.v10.2(20).02, 2020)
This paper provides a quantitative assessment of the 2007 - 2008 corporate and personal income tax reforms in Bulgaria. The simple investment model, based on Tobin’s q-theory is calibrated to Bulgarian data before and after the reform. Based on numerical simulations, capital stock is predicted to double over the long run.